Nociones de justicia: percepciones de la infancia. Del dicho al hecho (2020)
The research presents the results obtained during the development of the project “Social notions about justice built by boys and girls from official schools in the Kennedy district of Bogota.” It highlights the social notions of justice built by children in these institutions so that teachers can reflect on the design of alternatives to handle school conflict. The methodological reference is qualitative, based on the interpretative method, which provides a view from the categories studied. The analysis show that the participants have an ideal world in which justice should be the argument that regulates the application of the norms seeking freedom, equity, and equality in every sense.